Underwater bubble super-infiltration metal base material and nanosecond laser preparation method thereof
The anisotropic wettable surface is formed on the metal substrate by nanosecond laser preparation and surface modification method, which solves the problem of insufficient gas-liquid separation and achieves an efficient and low-cost gas-liquid separation effect.
Patent Information
- Application Number
- CN202510826541.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2025-08-29
AI Technical Summary
The prior art is difficult to efficiently prepare stable micro-nano structures on the surface of metal substrates, resulting in insufficient separation of gas-liquid phases, affecting the efficiency of industrial production and microfluidic operation, and the traditional methods are costly and complex.
The micro-nano composite structure is prepared on the surface of the metal substrate by using nanosecond laser, and the surface is modified by fluorosilane solution to form an anisotropic wettable surface of the underwater super-gasy and unprocessed surface underwater gas-like air-like, and the micro-nano-scale processing is achieved using the melt recasting effect of the nanosecond laser.
It has achieved a stable self-supporting surface structure, good gas-liquid separation effect, high processing efficiency and low cost, and is suitable for large-scale applications.
Smart Images

Figure CN120551583A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of micro-nano material preparation, and in particular relates to an underwater bubble super-wetting metal substrate and a nanosecond laser preparation method thereof. Background Art
[0002] Selective underwater bubble flow (gas-liquid separation) is a fundamental and critical step in many industrial processes, biochemical processes, and microfluidic operations. However, in many cases, insufficient separation of the gas and liquid phases hinders these applications. In fields such as petrochemicals, electronics manufacturing, and aerospace, the higher heat transfer coefficients and resistance of gas-liquid two-phase flow, coupled with unstable distribution, can lead to uneven flow distribution in heat transfer systems, steam generation in electronic cooling systems, and clogging of pipelines by gas byproducts in dye cells. In microfluidics, the failure of gas to exit microfluidic tubes in a timely manner can not only affect the normal flow rate of the liquid within the tubes, but can even block the microchannels, preventing liquid flow. In the field of hydrogen evolution by water electrolysis, the failure of bubbles to desorb from the electrode surface in a timely manner can create a "dead zone" in the reaction, reducing the reaction rate. Therefore, the ability to controllably remove bubbles from the liquid phase or to promptly separate the gas and liquid phases is an urgent problem in many fields.
[0003] Metal substrates, such as aluminum foil and nickel foam, are widely used in people's daily production and life due to their excellent properties of wear resistance, acid and alkali corrosion resistance, and high temperature resistance. However, due to their excellent stability, it is difficult to process their surfaces using common chemical reaction methods (such as chemical corrosion and self-assembly) to produce structures. For metal sheets such as commercial aluminum foil, it is difficult to directly generate micron pore arrays and stable surface roughness structures on the surface to assist underwater screening. Nickel foam is a porous grid structure, and it is difficult to prepare stable micro-nano structures on it without being impacted and dropped by the bubbles generated during the reaction.
[0004] In the paper ACS Appl.Mater.Interfaces, 2022, 14, 37, 42734-42743, the authors used a method of single-sided UV irradiation after chemical spraying to prepare hydrophilic / superhydrophobic (underwater aerobic / superaerobic) copper to achieve directional transmission of underwater bubbles. Compared with the laser preparation method, the steps are simple (one-step structure preparation), the material selection is wide (almost any metal material can be given a rich micro-nano structure on the surface), and it is flexible and controllable. It is a new type of micro-nano processing technology that can regulate the surface micro-nano structure and wettability. However, this method cannot prepare a stable self-supporting surface structure, and the preparation process is complicated and costly. Summary of the Invention
[0005] To address the aforementioned problems in the prior art, the present invention provides an underwater bubble super-wetting metal substrate and a nanosecond laser preparation method thereof. The technical problems to be solved by the present invention are achieved through the following technical solutions:
[0006] The embodiment of the present invention provides a nanosecond laser preparation method for underwater bubble super-wetting of a metal substrate, comprising the steps of:
[0007] Providing a metal substrate and cleaning the metal substrate to obtain a cleaned metal substrate;
[0008] Under first preset laser parameters, a nanosecond laser is used to perform direct write etching on the surface of the cleaned metal substrate to process a micro-nano composite structure, thereby obtaining a metal substrate having a composite structure; wherein the first preset laser parameters include: laser scanning speed, laser scanning spacing, laser average power, laser pulse frequency, laser pulse width, laser pulse wavelength, and processing method;
[0009] Cleaning and drying the metal substrate having the composite structure to obtain a dried metal substrate;
[0010] The dried metal substrate is immersed in a fluorosilane solution, and then dried to obtain an underwater super aerophilic metal substrate.
[0011] In one embodiment of the present invention, the metal substrate includes a metal sheet, a metal foam or a metal mesh.
[0012] In one embodiment of the present invention, in the first preset laser parameters, the laser pulse frequency is 20 kHz, the laser pulse width is 100 ns, the laser pulse wave length is 1030 nm, and the processing method includes any one of a bow-shaped scanning and a tic-tac-toe scanning;
[0013] When the metal substrate is a metal sheet, the laser scanning speed is 200 mm / s to 400 mm / s, the laser scanning interval is 50 μm, and the laser average power is 6 W to 8.5 W;
[0014] When the metal substrate is metal foam, the laser scanning speed is 200 mm / s to 400 mm / s, the laser scanning interval is 80 μm, the laser average power is 7 W to 8.5 W, and the number of processing times is 2 to 10;
[0015] When the metal substrate is a metal mesh, the laser scanning speed is 200 mm / s to 400 mm / s, the laser scanning interval is 50 μm, and the laser average power is 6 W to 8.5 W.
[0016] In one embodiment of the present invention, the fluorosilane solution is an anhydrous ethanol solution of 1H-1H-2H-2H-perfluorodecyltrimethoxysilane, wherein the volume ratio of H-1H-2H-2H-perfluorodecyltrimethoxysilane to anhydrous ethanol is 1:500.
[0017] In one embodiment of the present invention, the dried metal substrate is immersed in the fluorosilane solution for 18 hours to 30 hours;
[0018] The drying temperature after immersion is 60℃~100℃.
[0019] In one embodiment of the present invention, when the metal substrate is a metal sheet, after processing the micro-nano composite structure to obtain a metal substrate having a composite structure, the following steps are further included:
[0020] Under second preset laser parameters, a nanosecond laser is used to cut a through hole in the metal substrate with a composite structure; wherein the second preset laser parameters include: laser scanning speed, laser scanning spacing, laser average power, laser pulse frequency, laser pulse width, laser pulse wavelength and processing method.
[0021] In one embodiment of the present invention, in the second preset laser parameters, the laser pulse frequency is 20 kHz, the laser pulse width is 100 ns, the laser pulse wave length is 1030 nm; the laser scanning speed is 200 mm / s to 400 mm / s, the laser scanning interval is 50 μm, and the laser average power is 6 W to 8 W;
[0022] The processing method includes any one of circular cutting punching and percussion punching.
[0023] In one embodiment of the present invention, the size of the through holes is 20 μm to 500 μm, and the spacing between the through holes is 1 mm to 2 mm.
[0024] In one embodiment of the present invention, the contact angle between the processed surface of the underwater super aerophilic metal substrate and the underwater bubbles is 0° to 90°, and the contact angle between the unprocessed surface and the underwater bubbles is 0°.
[0025] Another embodiment of the present invention provides an underwater bubble super-wettable metal substrate, which is prepared by the preparation method described in the above embodiment.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] In the nanosecond laser preparation method of an underwater bubble super-wetting metal substrate of the present invention, a micro-nano composite structure is first prepared on the surface of the metal substrate using a nanosecond laser, and then the processed surface is modified with a low surface energy using a fluorosilane solution, and finally an underwater super-aerophilic metal substrate is prepared. The metal substrate has a stable structure and has a special wettability surface in which the processed surface is underwater super-aerophilic and the unprocessed surface is underwater aerophilic. The wettability of bubbles on the two surfaces is different. This anisotropic wettability surface can realize the unidirectional passage of underwater bubbles against buoyancy, thereby achieving the purpose of gas-liquid separation. At the same time, the processing is carried out using a nanosecond laser, which has a large power and a significant thermal effect. When the moving nanosecond laser point interacts with the material, a melting and recasting effect is generated. After the pulse energy is deposited, the material is heated and melted and splashed outward, and then cooled and recast, thereby realizing the processing of the micro-nano composite structure. The power during the processing is large, the processing efficiency is high, and the cost is low. Therefore, the preparation method not only realizes a stable self-supporting surface structure for gas-liquid separation, but also has a simple preparation process, high preparation efficiency, and low cost, which is conducive to large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A schematic flow chart of a nanosecond laser preparation method for underwater bubble super-wetting of a metal substrate provided by an embodiment of the present invention;
[0029] Figure 2 A schematic diagram of a nanosecond laser preparation process of an underwater bubble super-wettable aluminum foil film provided by an embodiment of the present invention;
[0030] Figure 3 An electron microscope image of an aluminum foil with gradient wettability underwater provided by an embodiment of the present invention;
[0031] Figure 4 Schematic diagram of the one-way anti-buoyancy transport of underwater bubbles by the Janus aluminum foil provided by the present invention;
[0032] Figure 5 A graph showing the relationship between the unidirectional gas transmission speed, the pore size, and the through-hole spacing provided in an embodiment of the present invention;
[0033] Figure 6 Schematic diagram of the rough surface structure of nickel foam after nanosecond laser processing provided by an embodiment of the present invention;
[0034] Figure 7 Schematic diagram of the rough surface structure of a stainless steel mesh after nanosecond laser processing provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0035] The present invention will be further described in detail below with reference to specific examples, but the embodiments of the present invention are not limited thereto.
[0036] See Figure 1 , Figure 1 A schematic flow chart of a nanosecond laser preparation method for underwater bubble super-wetting of a metal substrate provided by an embodiment of the present invention. The preparation method comprises the following steps:
[0037] S1. Providing a metal substrate and cleaning the metal substrate to obtain a cleaned metal substrate.
[0038] Specifically, the metal substrate includes a metal sheet, a metal foam, or a metal mesh. Exemplarily, the metal sheet includes aluminum foil, the metal foam includes nickel foam, and the metal mesh includes stainless steel mesh.
[0039] Specifically, the metal substrate is ultrasonically cleaned in anhydrous alcohol and deionized water in sequence.
[0040] S2. Under the first preset laser parameters, use nanosecond laser to perform direct writing etching on the surface of the cleaned metal substrate to process a micro-nano composite structure and obtain a metal substrate with a composite structure; wherein the first preset laser parameters include: laser scanning speed, laser scanning spacing, laser average power, laser pulse frequency, laser pulse width, laser pulse wavelength and processing method.
[0041] Specifically, in the first preset laser parameters, the laser pulse frequency is 20 kHz, the laser pulse width is 100 ns, the laser pulse wavelength is 1030 nm, and the processing method includes any one of bow-shaped scanning and tic-tac-toe scanning.
[0042] When the metal substrate is a metal sheet, the laser scanning speed is 200 mm / s to 400 mm / s, the laser scanning interval is 50 μm, and the laser average power is 6 W to 8.5 W.
[0043] When the metal substrate is metal foam, the laser scanning speed is 200 mm / s to 400 mm / s, the laser scanning interval is 80 μm, the average laser power is 7 W to 8.5 W, and the number of processing times, i.e., the number of laser scanning times, is 2 to 10 times.
[0044] When the metal substrate is a metal mesh, the laser scanning speed is 200 mm / s to 400 mm / s, the laser scanning interval is 50 μm, and the laser average power is 6 W to 8.5 W.
[0045] The manipulation of gas on the surface of super-wetting metal materials prepared by nanosecond laser is related to the surface structure and chemical composition of the material. For different types of metal substrates, the selection of laser scanning speed, laser scanning spacing and laser average power is an important influencing factor. This embodiment adopts different laser scanning speeds, laser scanning spacings and laser average power ranges for metal sheets, metal foams and metal meshes to achieve the preparation of micro-nano rough structures on the surface of each material. For each metal substrate, if the laser scanning speed, laser scanning spacing and laser average power change, the metal substrate finally prepared may not be able to achieve a super-aerophilic surface; for example, for metal sheets, when direct write etching is performed under the conditions of a laser scanning speed of 200mm / s to 400mm / s, a laser average power of 6W to 8.5W and a laser scanning spacing of 40μm or 60μm, the prepared metal substrates cannot achieve a super-aerophilic surface.
[0046] In this embodiment, the number of processing times on the metal foam surface is 2 to 10 times. Different numbers of laser scanning result in different rough structure thicknesses and depths, which changes the proportion of underwater super-aerophilic and general aerophilic materials, thereby resulting in different thickness ratios of different super-aerophilic and general aerophilic layers, and thus changes the water pressure that underwater bubbles need to break through, so the unidirectional transmission rate of bubbles can be controlled. Furthermore, the thicker the rough super-aerophilic layer, the faster the gas transmission speed.
[0047] Furthermore, under the first preset laser parameters, a nanosecond galvanometer method is used to perform nanosecond laser processing on one side of the metal substrate to produce a micro-nano composite structure.
[0048] In a specific embodiment, when the metal substrate is a metal sheet, after processing the micro-nano composite structure, the step is further included: using a nanosecond laser to cut a through hole in the metal substrate with the composite structure under a second preset laser parameter; wherein the second preset laser parameters include: laser scanning speed, laser scanning spacing, laser average power, laser pulse frequency, laser pulse width, laser pulse wavelength and processing method.
[0049] Specifically, the second preset laser parameters include a laser pulse frequency of 20kHz, a laser pulse width of 100ns, a laser pulse wavelength of 1030nm, a laser scanning speed of 200mm / s to 400mm / s, a laser scanning pitch of 50μm, and an average laser power of 6W to 8W. Processing methods include rotary drilling and percussion drilling.
[0050] Specifically, the shape of the processed through-holes is circular, the size of the through-holes is 20 μm to 500 μm, and the spacing between the through-holes is 1 mm to 2 mm.
[0051] In this embodiment, through holes are processed in the metal sheet, and bubbles can reach the processed surface from the unprocessed surface along the through holes. The bubble anti-buoyancy transmission speed can be controlled by adjusting the through hole size and the through hole spacing.
[0052] S3. Cleaning and drying the metal substrate with the composite structure to obtain a dried metal substrate.
[0053] Specifically, the metal substrate with the composite structure obtained in step S2 is ultrasonically cleaned in anhydrous alcohol and deionized water in sequence, and then the cleaned sample is placed in a nitrogen environment for drying at room temperature.
[0054] S4. Immersing the dried metal substrate in a fluorosilane solution, and drying after immersion to obtain an underwater super-aerophilic metal substrate.
[0055] Specifically, the single-sided roughened metal substrate obtained in step S3 is immersed in a fluorosilane solution at room temperature for 18 to 30 hours. During the immersion process, fluoroalkylsilane molecules spontaneously deposit on the metal substrate surface, thereby modifying the original surface energy. Finally, the immersed sample is dried at 60°C to 100°C for 2 hours to ensure the stability of the fluoroalkylsilane molecular layer.
[0056] Specifically, the fluorosilane solution is an anhydrous ethanol solution of 1H-1H-2H-2H-perfluorodecyltrimethoxysilane, wherein the volume ratio of H-1H-2H-2H-perfluorodecyltrimethoxysilane to anhydrous ethanol is 1:500, that is, the mass fraction of fluorosilane is 0.2%.
[0057] The mass fraction of fluorosilane in this embodiment is 0.2%. The fluoroalkylsilane molecules spontaneously deposit on the surface of the metal substrate to achieve surface modification of the sample. If the mass fraction of fluorosilane becomes smaller, there are fewer carbon-fluorine chains in the fluorosilane, and super-aerophilicity cannot be achieved in the material. If the mass fraction of fluorosilane increases, the fluorosilane will form a film on the surface of the material and cannot form molecular chains on the surface of the material, and the water transport effect cannot be achieved.
[0058] In the nanosecond laser preparation method of an underwater bubble super-wetting metal substrate of the present embodiment, a micro-nano composite structure is first prepared on the surface of the metal substrate using a nanosecond laser. The processed surface is then modified with a fluorosilane solution to reduce the surface energy, and finally an underwater super-aerophilic metal substrate is prepared. The metal substrate has a stable structure and a special wettability surface with underwater super-aerophilicity on the processed surface and underwater aerophilicity on the unprocessed surface. The wettability of bubbles on the two surfaces is different. This anisotropic wettability surface can achieve unidirectional passage of underwater bubbles against buoyancy, thereby achieving the purpose of gas-liquid separation. At the same time, compared with femtosecond laser processing, the nanosecond laser power is higher and the thermal effect is significant. When the moving nanosecond laser point interacts with the material, a melting and recasting effect is generated. After the pulse energy is deposited, the material is heated and melted and splashed outward, and then cooled and recast, thereby achieving the processing of the micro-nano composite structure. The processing power is high, the processing efficiency is high, and the cost is low. Therefore, the preparation method not only achieves a stable self-supporting surface structure for gas-liquid separation, but also has a simple preparation process, high preparation efficiency, and low cost, which is conducive to large-scale promotion and application.
[0059] For the convenience of understanding the present invention, the present invention is given below with examples. It should be understood by those skilled in the art that the examples are only for the purpose of helping to understand the present invention and should not be regarded as specific limitations of the present invention.
[0060] Example 1
[0061] See Figure 2 , Figure 2 Schematic diagram of a nanosecond laser preparation process for an underwater bubble super-wetting aluminum foil film provided by an embodiment of the present invention. This embodiment provides a nanosecond laser preparation method for an underwater bubble super-wetting aluminum foil film, the preparation method comprising the following steps:
[0062] S1. Select an aluminum foil substrate of different thicknesses according to the specific environment. For example, a 50 μm thick aluminum foil is selected. Clean the aluminum foil with acetone, anhydrous ethanol, and deionized water in sequence, with each solvent cleaning time being 10 minutes.
[0063] S2. Place the aluminum foil cleaned in step S1 on a processing table and set the first preset laser parameters: nanosecond laser Gaussian pulse light pulse width of 100 ns, laser pulse frequency of 20 kHz, laser pulse wavelength of 1030 nm, laser average power of 6 W, processing speed of 200 mm / s, processing interval of 50 μm, call the pre-programmed control laser scanning mode to bow-shaped line-by-line scanning, only perform laser processing on one side of the aluminum foil, and process the micro-nano composite structure.
[0064] S3. The aluminum foil obtained by pre-processing in step S2 is placed without changing its placement. After adjusting the parameters, a microhole array is prepared in situ, and the second preset laser parameters for punching are: laser pulse frequency is 20 kHz, laser pulse width is 100 ns, and laser pulse wave commitment is 1030 nm; laser scanning speed is 200 mm / s, laser scanning spacing is 50 μm, and laser average power is 8 W. The pre-programmed control laser scanning mode is circular scanning.
[0065] S4. The aluminum foil obtained in step S2 is ultrasonically cleaned in anhydrous alcohol and deionized water in sequence, with each solvent cleaning time being 10 minutes. The cleaned sample is then placed in a nitrogen environment for drying at room temperature.
[0066] S5. Soak the single-sided rough porous aluminum foil obtained in step S4 in a fluorosilane solution and soak it at room temperature for 24 hours. The fluorosilane solution is prepared with a volume fraction ratio of 1H-1H-2H-2H-perfluorodecyltrimethoxysilane: anhydrous ethanol = 1:500. During the soaking process, the fluoroalkylsilane molecules spontaneously deposit on the surface of the aluminum foil, and this process completes the low surface energy modification of the original surface. Finally, the soaked sample is heated at 100°C in a high-temperature furnace for 2 hours to ensure the stability of the fluoroalkylsilane molecular layer. After the soaking, an underwater super-aerophilic aluminum foil (i.e., underwater bubbles directional penetrating Janus aluminum foil) is obtained. Among them, Janus refers to the different properties of the processed surface and the unprocessed surface.
[0067] See Figure 3 , Figure 3 This is an electron microscope image of an aluminum foil with gradient wettability under water provided by an embodiment of the present invention, wherein (a) to (d) are processed surfaces, (e) to (f) are unprocessed surfaces, and (h) to (i) are elemental analyses of the processed surfaces. Figure 3 In (a) to (d), it can be clearly seen that the surface of the material is distributed with micron-scale corrugated structures. The edge size of the structure is about 5μm, the center is relatively smooth, and the structural period is about 20μm. This is the melting and recasting effect when the moving laser point interacts with the material. After the pulse energy is deposited, the material is heated and melted and splashed outward, and then cooled and recast. The periodic corrugated structure increases the roughness of the aluminum foil surface. The defects caused by processing increase the surface energy of the material, thereby enhancing the intrinsic wettability. The wettability gradient caused by the structural difference between the upper and lower surfaces of the aluminum foil is crucial for the transmission of bubbles. At the same time, a micron array of through holes is formed after processing, and the upper and lower hole sizes of the through holes processed by circumferential cutting are not much different. From Figure 3 From (e) to (f), it can be seen that there is no particle sputtering in the unprocessed area, showing a smooth surface. Figure 3As can be seen from (h) to (i) in the figure, nanosecond laser one-step processing can not only increase the surface roughness, but also simultaneously generate metal oxides, which increases the surface energy and further increases the underwater superaerophilicity.
[0068] See Figure 4 , Figure 4 Schematic diagram of the unidirectional anti-buoyancy transport of underwater bubbles by the Janus aluminum foil provided by the present invention. Specifically, the Janus aluminum foil is immersed in water with the unprocessed surface facing down and the processed surface facing up. A large number of bubbles are released under the sample, and when the bubbles contact the lower surface of the sample, they are quickly sucked into the upper surface and spread, which means that the bubbles can pass from the lower surface (unprocessed surface) to the upper surface (processed surface). This is equivalent to turning on the bubble switch. In order to eliminate the influence of buoyancy, the sample is turned over, that is, the processed surface faces down and the unprocessed surface faces up, and a small bubble is squeezed out at the tip of the micro-injector, and the bubble is still introduced from the direction of the unprocessed surface (i.e., the upper surface). The moment the bubble contacts the upper surface, it is quickly sucked to the lower surface and spreads. This reflects that the bubble can be transported from top to bottom against buoyancy, further confirming the good unidirectional transportability of the Janus surface. Figure 4 As shown. Conversely, when bubbles are introduced from the lower surface, they spread out and are blocked by the aluminum foil. As the number of bubbles increases, even with a strong buoyancy, they are still blocked and cannot pass through. This result demonstrates that a one-way bubble-conducting Janus membrane can be easily prepared using single-sided laser scanning combined with surface energy modification. Bubbles can only conduct from the underwater aerophilic surface to the underwater superaerophilic surface, and are blocked in the opposite direction. This characteristic is similar to the unidirectional conduction of current in a diode in an electrical circuit, and this one-way bubble-conducting membrane is called a "bubble diode."
[0069] The unidirectional conduction property of the underwater bubble of the "bubble diode" can be explained by the force applied to the bubble when it contacts the surface. For the case where the unprocessed surface is facing downward, the moment the bubble contacts the smooth surface that is generally air-friendly, it is subjected to three forces, namely, the upward buoyancy force (F B ), the upward Laplace force (F L ) and the downward resistance exerted by the stainless steel mesh (F R ). Since the unprocessed surface is modified with a layer of CF molecular chains, a thin layer of air is captured on it, showing the general air affinity underwater. On the contrary, due to the large roughness and low surface energy modification of the upper surface, a thick layer of air can be captured. After the air bubble contacts the surface, the air bubble, the thin air layer, and the thick air layer together form a gas channel, connecting the air layer above and below the stainless steel mesh with the air bubble. In the vertical direction of F L and F BUnder the combined effect of F, the bubbles can quickly pass through the stainless steel mesh and spread on the processing surface (super air-friendly surface). However, when the bubbles first contact the processing surface, the bubbles are affected by the upward F B , downward F R and the lateral F along the horizontal direction L In this state, the bubbles tend to be more L Under the action of the spread along the processing surface, the vertical direction F B and F R Maintain balance. When the unprocessed surface is facing upwards, the bubble is subjected to only two forces when it contacts the upper surface: F B and F L , when the gas channel is connected, according to the Young-Laplace formula, due to the difference in bubble radius on the upper and lower surfaces, the Laplace pressure on the upper and lower surfaces will be different, resulting in a pressure difference:
[0070]
[0071] Where: ΔF L is the Laplace pressure difference, R b is the bubble contact surface radius, R g is the radius of the original trapped gas layer, γ w is the surface tension of water, which is 7.2×10 -2 N / m.
[0072] When a 6μL bubble contacts the underwater air-friendly surface, R is calculated based on the measured contact angle. b The value is about 2.318mm. Because after the aluminum foil is immersed in water, the contact angle of the air layer captured by the underwater superaerophilic surface is about 0°, and the gas radius can be regarded as infinite, so The value of is infinitely close to 0, and we get ΔF L The value of is about 31Pa, so the Laplace force F on the bubble is L The size is about 127.66μN. At this time, the buoyancy force on the bubble is about 6μN. It can be concluded that the Laplace force F generated by the asymmetric wettability difference between the upper and lower surfaces L Much larger than the buoyancy F B , so the bubbles can overcome the upward buoyancy and perform self-driven anti-buoyancy transport.
[0073] See Figure 5 , Figure 5 A graph showing the relationship between the unidirectional gas transmission speed, the aperture size, and the through-hole spacing provided in an embodiment of the present invention, wherein the ordinate is the aperture size and the abscissa Length is the through-hole spacing. Figure 5In the figure, the darker the color, the faster the bubble transmission speed. When the pore diameter is 200μm and the pore spacing is 1mm, the bubble transmission speed is the fastest, at approximately 43ms. The transmission speed increases with increasing pore diameter and decreasing pore spacing. At a fixed spacing, the unidirectional transmission speed initially increases with increasing pore size. As the pore size further increases, the difference in wettability between the front and back surfaces decreases, and the transmission speed decreases.
[0074] Example 2
[0075] This embodiment provides a nanosecond laser preparation method for underwater bubble super-wetting nickel foam, which comprises the following steps:
[0076] S1. Select nickel foam of different thickness and composition according to the specific environment. For example, select nickel foam with a thickness of 1 mm. Clean the nickel foam with acetone, anhydrous ethanol, and deionized water in sequence, with each solvent cleaning time being 10 minutes.
[0077] S2. Place the nickel foam obtained by cleaning in step S1 on a processing table, set the first preset laser parameters: nanosecond laser Gaussian pulse light pulse width of 100 ns, laser pulse frequency of 20 kHz, laser pulse wavelength of 1030 nm, laser average power of 8.5 W, processing speed of 400 mm / s, processing interval of 80 μm, processing times of 5 times, call the pre-programmed control laser scanning mode to bow-shaped line scanning, only perform laser processing on one side of the nickel foam, and process a micro-nano composite structure.
[0078] See Figure 6 , Figure 6 This is a schematic diagram of the rough surface structure of nickel foam after nanosecond laser processing provided by an embodiment of the present invention. Figure 6 The middle left picture is the processing surface. Figure 6 The image on the right is a magnified electron micrograph of the surface structure. After nanosecond laser processing, the smooth mesh of the metal foam surface is segmented into a multi-level, micron-scale roughened composite structure. Different processing times can lead to different depths of roughness, resulting in different proportions of different wettability surfaces across the thickness.
[0079] S3. The nickel foam obtained in step S2 is ultrasonically cleaned in anhydrous alcohol and deionized water in sequence, with each solvent cleaning time being 10 minutes. The cleaned sample is then placed in a nitrogen environment for drying at room temperature.
[0080] S4. Soak the single-sided rough nickel foam obtained in step S3 in a fluorosilane solution and soak it at room temperature for 24 hours. The fluorosilane solution is prepared with a volume fraction ratio of 1H-1H-2H-2H-perfluorodecyltrimethoxysilane: anhydrous ethanol = 1:500. During the soaking process, the fluoroalkylsilane molecules spontaneously deposit on the surface of the nickel foam, and this process completes the low surface energy modification of the original surface. Finally, the soaked sample is heated at 100°C in a high-temperature furnace for 2 hours to ensure the stability of the fluoroalkylsilane molecular layer. After the soaking, underwater super-aerophilic nickel foam (i.e., underwater bubble-directionally penetrating Janus nickel foam) is obtained.
[0081] Example 3
[0082] This embodiment provides a nanosecond laser preparation method for underwater bubble super-wetting stainless steel wire mesh, which comprises the following steps:
[0083] S1. Select a stainless steel mesh with different mesh sizes according to the specific environment. For example, a stainless steel mesh with a mesh size of 300 is selected. The nickel foam is cleaned with acetone, anhydrous ethanol, and deionized water in sequence, with each solvent cleaning time being 10 minutes.
[0084] S2. Place the stainless steel mesh cleaned in step S1 on a processing table and set the first preset laser parameters: nanosecond laser Gaussian pulse light pulse width of 100 ns, laser pulse frequency of 20 kHz, laser pulse wavelength of 1030 nm, laser average power of 9.5 W, processing speed of 400 mm / s, processing interval of 50 μm, processing times of 1, call the pre-programmed control laser scanning mode to bow-shaped line-by-line scanning, and perform laser processing on only one side of the stainless steel mesh to process a micro-nano composite structure.
[0085] See Figure 7 , Figure 7 This is a schematic diagram of the rough surface structure of the stainless steel mesh after nanosecond laser processing provided by an embodiment of the present invention. Figure 7 The left picture is a side view electron microscope picture, the upper surface has processing marks, and the lower surface is not processed. Figure 7 The image on the right is a top-down electron microscope image. After nanosecond laser processing, the smooth mesh wires on the stainless steel mesh surface are periodically cut. Simultaneously, due to the strong melt recasting effect, a large number of micro-nano composite rough structures and nanoscale tiny holes are generated on the surface.
[0086] S3. The stainless steel mesh obtained in step S2 was ultrasonically cleaned in anhydrous alcohol and deionized water in sequence, with each solvent cleaning time being 10 minutes. The cleaned sample was then placed in a nitrogen environment for drying at room temperature.
[0087] S4. Soak the single-sided rough stainless steel mesh obtained in step S3 in a fluorosilane solution and soak it at room temperature for 24 hours. The fluorosilane solution is prepared with a volume fraction ratio of 1H-1H-2H-2H-perfluorodecyltrimethoxysilane: anhydrous ethanol = 1:500. During the soaking process, the fluoroalkylsilane molecules spontaneously deposit on the surface of the nickel foam, and this process completes the low surface energy modification of the original surface. Finally, the soaked sample is heated at 100°C in a high-temperature furnace for 2 hours to ensure the stability of the fluoroalkylsilane molecular layer. After the soaking, underwater super-aerophilic nickel foam is obtained (i.e., underwater bubbles directionally penetrate the Janus stainless steel mesh).
[0088] In this embodiment, a single side of the stainless steel mesh is processed using a nanosecond laser, so that the structure and wettability of the upper and lower surfaces of the stainless steel mesh are differentiated. The processed rough surface is an underwater super-bubble-friendly surface, and the unprocessed surface is a general air-friendly surface. This causes the bubbles to be squeezed to the processed surface by the Laplace pressure difference the moment they come into contact with the unprocessed surface, thereby realizing rapid unidirectional bubble transmission.
[0089] The embodiments of the present invention are based on a method of nanosecond laser one-step direct writing combined with surface chemical modification. Micro-nano rough structures are prepared on the surfaces of aluminum foil, nickel foam, and stainless steel mesh, and micron-scale through holes are prepared on the aluminum foil, thereby realizing a gas directional transmission scheme for underwater bubbles on the surfaces of various metal materials with anti-buoyancy transport. The raw materials used in this method are inexpensive, and the size of the mesh can be adjusted according to actual conditions. The metal film, metal mesh, and metal foam have stable performance and are widely used in industry. The manipulation of gas on the surface of the super-wetting metal material prepared by nanosecond laser is only related to the surface structure and chemical composition, and has nothing to do with the type and properties of the bubbles. Therefore, this method is applicable to various gases. The underwater bubble super-wetting metal substrate prepared by the embodiments of the present invention can be applied to fields such as seabed methane collection, removal of bubbles adhering to container surfaces, and timely desorption of bubbles on the surface of electrochemical reaction electrodes, to a certain extent solving environmental pollution and energy problems.
[0090] The above is a further detailed description of the present invention in conjunction with specific preferred embodiments, and the specific implementation of the present invention should not be considered to be limited to these descriptions. For those skilled in the art of the present invention, without departing from the concept of the present invention, several simple deductions or substitutions can be made, which should be considered to fall within the scope of protection of the present invention.
Claims
1. A nanosecond laser preparation method for underwater bubble super-wetting of metal substrates, characterized in that: Including steps: Providing a metal substrate and cleaning the metal substrate to obtain a cleaned metal substrate; Under first preset laser parameters, a nanosecond laser is used to perform direct write etching on the surface of the cleaned metal substrate to process a micro-nano composite structure, thereby obtaining a metal substrate having a composite structure; wherein the first preset laser parameters include: laser scanning speed, laser scanning spacing, laser average power, laser pulse frequency, laser pulse width, laser pulse wavelength, and processing method; Cleaning and drying the metal substrate having the composite structure to obtain a dried metal substrate; The dried metal substrate is immersed in a fluorosilane solution, and then dried to obtain an underwater super aerophilic metal substrate.
2. The nanosecond laser preparation method for underwater bubble super-wetting of metal substrate according to claim 1, characterized in that: The metal substrate includes a metal sheet, a metal foam or a metal mesh.
3. The nanosecond laser preparation method for underwater bubble super-wetting of metal substrate according to claim 1, characterized in that: In the first preset laser parameters, the laser pulse frequency is 20 kHz, the laser pulse width is 100 ns, the laser pulse wave length is 1030 nm, and the processing method includes any one of bow-shaped scanning and tic-tac-toe scanning; When the metal substrate is a metal sheet, the laser scanning speed is 200 mm / s to 400 mm / s, the laser scanning interval is 50 μm, and the laser average power is 6 W to 8.5 W; When the metal substrate is metal foam, the laser scanning speed is 200 mm / s to 400 mm / s, the laser scanning interval is 80 μm, the laser average power is 7 W to 8.5 W, and the number of processing times is 2 to 10; When the metal substrate is a metal mesh, the laser scanning speed is 200 mm / s to 400 mm / s, the laser scanning interval is 50 μm, and the laser average power is 6 W to 9.5 W.
4. The nanosecond laser preparation method for underwater bubble super-wetting of metal substrate according to claim 1, characterized in that: The fluorosilane solution is an anhydrous ethanol solution of 1H-1H-2H-2H-perfluorodecyltrimethoxysilane, wherein the volume ratio of H-1H-2H-2H-perfluorodecyltrimethoxysilane to anhydrous ethanol is 1:
500.
5. The nanosecond laser preparation method for underwater bubble super-wetting metal substrate according to claim 1, characterized in that: The dried metal substrate is immersed in the fluorosilane solution for 18 to 30 hours; The drying temperature after immersion is 60℃~100℃.
6. The nanosecond laser preparation method for underwater bubble super-wetting of metal substrate according to claim 1, characterized in that: When the metal substrate is a metal sheet, after processing the micro-nano composite structure to obtain a metal substrate with a composite structure, the following steps are further included: Under second preset laser parameters, a nanosecond laser is used to cut a through hole in the metal substrate with a composite structure; wherein the second preset laser parameters include: laser scanning speed, laser scanning spacing, laser average power, laser pulse frequency, laser pulse width, laser pulse wavelength and processing method.
7. The nanosecond laser preparation method for underwater bubble super-wetting of metal substrate according to claim 6, characterized in that: In the second preset laser parameters, the laser pulse frequency is 20 kHz, the laser pulse width is 100 ns, the laser pulse wave length is 1030 nm; the laser scanning speed is 200 mm / s to 400 mm / s, the laser scanning interval is 50 μm, and the laser average power is 6 W to 8 W; The processing method includes any one of circular cutting punching and percussion punching.
8. The nanosecond laser preparation method for underwater bubble super-wetting of metal substrate according to claim 6, characterized in that: The size of the through holes is 20 μm to 500 μm, and the spacing between the through holes is 1 mm to 2 mm.
9. The nanosecond laser preparation method for underwater bubble super-wetting of metal substrate according to claim 1, characterized in that: The contact angle between the processed surface of the underwater super aerosol-friendly metal substrate and the underwater bubbles is 0° to 90°, and the contact angle between the unprocessed surface and the underwater bubbles is 0°.
10. An underwater bubble super-wetting metal substrate, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.